The transforming power of cultural rights : a promising law and humanities approach / Helle Porsdam. - Porsdam, Helle, 1956- (Cambridge University Press, 2019)
Cultural rights promote cultural and scientific creativity. Transformative and empowering, they also enable the pursuit of knowledge and understanding, thereby working as atrocity prevention tools. The Transforming Power of Cultural Rights argues that this gives these rights a central role to play in promoting the full human personality and in realizing all other human rights. Looking at the work of the UN Special Rapporteurs in the field of cultural rights as well as UNESCO's efforts, Helle Porsdam addresses the question of how a universal human rights agenda can include a dialogue that recognizes the importance of cultural diversity without sliding into cultural relativism. She argues that cultural rights offer a useful international arena and discourse in which to explain and negotiate cultural meanings when controversies arise. This places them at the center of human rights - and at the center of law and humanities.